Information leakage, imitation, and the patent system - Dirk Czarnitzki; Kristof van Criekingen (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
From a firm's perspective two competing forces are driving the decision to invest in innovation. On the one hand, innovative performance is an important driver of profitability and growth. On the other hand, investments in innovation suffer from negative externalities, i.e. spillovers to other firms, and hence imitation could be induced. To preempt imitation firms may protect their inventions by means of intellectual property rights, such as patents. By taking out a patent, however, a firm also conveys information about the functioning of the invention to competitors. In this empirical paper, we highlight the trade-off of patenting by setting up a recursive system of equations on knowledge leakage and imitation that, among other factors, may be partly determined by firms' patenting activity. Thereby we contribute to the debate on the functioning of the contemporary patent system. We find that patenting firms are being less confronted with imitation. The effect of patents on the dissemination of R&D findings is, however, insignificant. Therefore, we conclude that patent disclosures do not significantly harm the appropriability conditions for inventions, but help to protect, at least partly, against imitation, as it has been originally envisaged by policy.
Keywords: O31; O33; O34; O38; 330; Innovation; R&D; Imitation; Dissemination; Patents